2013
DOI: 10.1021/jf403564s
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis and Cell Cycle Arrest in A549 Human Lung Adenocarcinoma Cells by Surface-Capping Selenium Nanoparticles: An Effect Enhanced by Polysaccharide–Protein Complexes from Polyporus rhinocerus

Abstract: Surface-capping agents play key roles in cellular uptake and biological activity of functional nanomaterials. In the present study, functionalized selenium nanoparticles (SeNPs) have been successfully synthesized using Polyporus rhinocerus water-soluble polysaccharide-protein complexes (PRW) as the capping agent during the reduction of selenium salts. The acquired monodisperse, spherical PRW-SeNPs presented desirable size distribution and stability in the solution. Moreover, PRW surface decoration significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 117 publications
(58 citation statements)
references
References 36 publications
3
55
0
Order By: Relevance
“…Typical apoptotic changes included chromatin condensation, chromatin compaction along the periphery of the nucleus, and segmentation of the nucleus (Wu et al, 2013). In order to confirm the effect of WECF on the cells' anti-apoptosis, DAPI staining, which is used to compare the native of the chromatin condensation of treated cells and control cells, is used.…”
Section: Resultsmentioning
confidence: 99%
“…Typical apoptotic changes included chromatin condensation, chromatin compaction along the periphery of the nucleus, and segmentation of the nucleus (Wu et al, 2013). In order to confirm the effect of WECF on the cells' anti-apoptosis, DAPI staining, which is used to compare the native of the chromatin condensation of treated cells and control cells, is used.…”
Section: Resultsmentioning
confidence: 99%
“…13,14 Selenium (Se) is a mineral trace element of fundamental importance to humans and animals. 15 The role of Se as a potential cancer chemotherapeutic and chemopreventive agent has been supported by many epidemiological, preclinical, and clinical studies. 16 Previous studies have shown that Se was degradable in vivo, and the degraded Se could be used as a nutrient for many kinds of normal cells or as an antiproliferative agent for many kinds of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence suggests that fabrication of nanomaterials with bioactive polysaccharide may have several advantages [15, 16]. Ulva lactuca polysaccharide (ULP) displays several physicochemical and biological features of interest for food, pharmaceutical, agricultural, and chemical applications.…”
Section: Introductionmentioning
confidence: 99%